Stroke-Like Presentation Following Febrile Seizure in a Patient with 1q43q44 Deletion Syndrome - Robinson, J. Elliott; Wolfe, Stephanie M.; Kaiser-Rogers, Kathleen; Greenwood, Robert S. (Frontiers in Neurology, 2016)
Hemiconvulsion-hemiplegia-epilepsy syndrome (HHE) is a rare outcome of prolonged hemiconvulsion that is followed by diffuse unilateral hemispheric edema, hemiplegia, and ultimately hemiatrophy of the affected hemisphere and epilepsy. Here we describe the case of a 3-year old male with a 1;3 translocation leading to a terminal 1q43q44 deletion and a terminal 3p26.1p26.3 duplication that developed HHE after a prolonged febrile seizure and discuss the pathogenesis of HHE in the context of the patient’s complex genetic background.